Sustainable development and rural poverty in the Republic of Ireland : review artiicle - Crowley, Ethel (Economic & Social Studies, 1998)
When one embarks upon a conversation about anything to do with rural Ireland, the most common perception one encounters is that farmers "are cleaning up" or "creaming off the system", that farmers are, for example, absorbing most of the benefits from the EU, and are still controlling politics. These perceptions have grown to the status of modern myths among city and town-dwellers, and like most myths, contain some grain of truth but are generally blown out of all proportion.
Keywords: Sustainable development; Rural poverty; Ireland; Review article